Assessment Of Hospital Information System In Selected Hospitals In Tehran - Esmaeel Mehraeen; Maryam Ahmadi; Maedeh Shajarat; Masumeh Khoshgam (Tehran University of Medical Sciences, 2013)
Background and Aim: According to the objectives of the information systems and to avoid duplication and help to improve the quality of care and reduce costs, HIS ongoing evaluation should be conducted to achieve these goals. This study has evaluated hospital information systems in selected hospitals with the use of "integrated hospital information system evaluation criteria-2011". Materials and Methods: This study was a descriptive-sectional research. The study population consisted of information systems in Shohada, Rsool Akram, Khatamolanbia, Imam Khomeyni and Milad hospitals. The data collection tool was a checklist of HIS indicators. Checklist was completed with direct observation and interviews with HIS users in selected hospitals. Data was analyzed by SPSS statistical software, and results were presented in statistical tables and charts. Results: In the studied hospitals most of the subtypes of organizational and server components of the hospital information system has been set up and used. However, pharmacy, decision support, medical services, communication services and telemedicine information systems, are not yet fully set up in the studied hospitals. Conclusion: Most subtypes of organizational and server components, currently exist in all fields in the studied hospitals.